TEACHING MATHEMATICS WITH NEW TECHNOLOGIES, SOME PERCEPTIONS OF EFFECTIVENESS OF ICT USE IN MOROCCO - Hamdane, Karima; Khaldi, Mohamed; Bouzinab, Ali (European Scientific Journal, ESJ, 2014)
Many countries are realizing the importance of equipping their educational institutions to the new technology of connection, information and communication. Connectivity provides many benefits, including access to an ever-growing volume of educational information, opportunities for collaboration and the use of online applications. In addition, it is important for students, as well as teachers, to learn information and communication technology (ICT) skills to enable them to participate in the evolving knowledge society. The Moroccan government is heavily investing in human and physical capital and has undertaken important regulatory reforms in order to introduce this tool in teaching. This paper highlights the efforts in this regard and describes some aspects of teaching mathematics using ICT, benefits and constraints and stakeholders who can promote the integration of this tool in the process of teaching and learning.